2021
DOI: 10.1021/acsaem.0c02727
|View full text |Cite
|
Sign up to set email alerts
|

2D/2D Nb3O7F/g-C3N4 Heterojunction Photocatalysts with Enhanced Hydrogen Evolution Activity

Abstract: Constructing two-dimensional (2D)/2D heterojunctions with intimate interfacial contact is of great importance to achieve high photocatalytic efficiency for hydrogen evolution. Herein, 2D/2D niobium oxyfluoride (Nb 3 O 7 F)/graphitic carbon nitride (g-C 3 N 4 ) heterojunction photocatalysts were prepared by a two-step hydrothermal/calcination method. As expected, the obtained 2D/2D Nb 3 O 7 F/g-C 3 N 4 heterojunctions exhibited a high photocatalytic hydrogen evolution rate of 1242.0 μmol h −1 g −1 , which was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Recently, Wang et al reported a 2D/2D g-C 3 N 4 /In 2 S 3 photocatalyst for photocatalytic H 2 O 2 production . Similarly, Li and his group members designed a 2D/2D Nb 3 O 7 F/g-C 3 N 4 heterojunction for photocatalytic H 2 evolution . However, a few numbers of tungsten disulfide-modified g-C 3 N 4 heterostructures have been reported; however, to our information, nonmetal-doped g-C 3 N 4 -based S-scheme heterojunctions with 2D WS 2 have not been investigated yet.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Recently, Wang et al reported a 2D/2D g-C 3 N 4 /In 2 S 3 photocatalyst for photocatalytic H 2 O 2 production . Similarly, Li and his group members designed a 2D/2D Nb 3 O 7 F/g-C 3 N 4 heterojunction for photocatalytic H 2 evolution . However, a few numbers of tungsten disulfide-modified g-C 3 N 4 heterostructures have been reported; however, to our information, nonmetal-doped g-C 3 N 4 -based S-scheme heterojunctions with 2D WS 2 have not been investigated yet.…”
Section: Introductionmentioning
confidence: 82%
“…32 Similarly, Li and his group members designed a 2D/2D Nb 3 O 7 F/g-C 3 N 4 heterojunction for photocatalytic H 2 evolution. 33 However, a few numbers of tungsten disulfide-modified g-C 3 N 4 heterostructures have been reported; however, to our information, nonmetal-doped g-C 3 N 4 -based S-scheme heterojunctions with 2D WS 2 have not been investigated yet. Encouraged by the above discussion, we have synthesized a 2D−2D WS 2 decorated SCN heterojunction composite by using wet impregnation and calcination techniques, as illustrated in Scheme 1.…”
Section: ■ Introductionmentioning
confidence: 84%
“…2.9–3.2 eV, as well as low cost and high chemical stability. Nb 3 O 7 F is a commonly used material for a variety of applications including catalysts, sensors, recording materials, electrochemical supercapacitors, Li-ion batteries, and field emission materials ( Idrees et al, 2014 ; Hirai et al, 2018 ; Chen et al, 2021 ; Li et al, 2021 ; Zhang et al, 2021 ). However, Au combined with Nb 3 O 7 F had been never investigated before, including photocatalytic degradation of contaminants in water.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies in the field of photocatalytic disinfection focused on constructing a heterojunction composite to address these concerns. 8 The energy band offset occurring at the interface between the components within a composite material generates an internal electric field that governs the direction of transfer and results in the spatial separation of electrons and holes. Often, an increase in surface area with the incorporation of other materials confers the composite with an extended light harvesting capability.…”
Section: Introductionmentioning
confidence: 99%
“…Graphitic carbon nitride (g-C 3 N 4 ) holds great potential as a green photocatalyst owing to its metal-free nature, visible-light activity, facile and scalable synthesis, high chemical and thermal stability, and ease of functionalization due to its polymeric chain tunability and two-dimensional (2D) characteristic. , Its photocatalytic performance, however, is suppressed by high charge recombination, insufficient absorption of visible light, and low surface area. Prior studies in the field of photocatalytic disinfection focused on constructing a heterojunction composite to address these concerns . The energy band offset occurring at the interface between the components within a composite material generates an internal electric field that governs the direction of transfer and results in the spatial separation of electrons and holes.…”
Section: Introductionmentioning
confidence: 99%